Profesionalna etika socialnega dela v ZDA - Maučec, Branka (Socialno delo, 2007)
The practice of social work complies to a great extent with the principles and standards as outline in the Code of Ethics and the code of conduct of social care institutions, as well as with local, state and federal legislature. On the one hand, those legal documents provide support to decision-making and assisstance to the practitioners of social work services.However, they can also expose social workers to the dilemma of how to address highly complex ethical questions and at the same time remain within the bounderies of their personal ethical concern. This study addresses the evolution of ethics within the development of the US system of social work nand outlines the areas of risk social workers have been facing through exposure to malpractice suits. Furthermore, the study analyses some ethical complaints presented to the National Association of Social Workers, and presents the strategies of risk management and mitigation as the mechanisms of fundamental importance for the competent practice and performance of social work.
Keywords: etični kodeksi; profesionalna etika; social work; socialno delo; United States of America; ZDA